The electrophysiology of ionotropic glutamate receptors expressed in human cell lines, HEK293 and TE671 - Newman, Amy (2022)
Ionotropic glutamate receptors consist of NMDA, AMPA and kainate receptors and are responsible for the conduction of synaptic transmission, long term potentiation, and synaptic plasticity and are implicated in a wide range of neurological diseases. Human models of these receptors are difficult to produce, and the majority of the data gathered is from the expression of these receptors in Xenopus oocytes and mice and rat models, which produce data that is less applicable to humans. There is a requirement of human models of these receptors, due to their associations with various human diseases, so it is necessary to produce valid and applicable results. This study demonstrates two potential human in vitro models, one for kainate receptors in the human cell line HEK293, and another for potentially all three types of ionotropic glutamate receptor in the human cell line TE671. The kainate receptor subunit GluK2 was expressed in HEK293 cells after transfection with the Escort IV reagent and our evidence suggests that all three ionotropic glutamate receptors are expressed in TE671 cells that have been differentiated by db-cAMP. The differentiated TE671 cells present an altered morphological cell type, that identify more with neuronal cells, rather than muscle cells, which are the usual morphological phenotype of TE671 cells under normal physiological conditions. The response of native nicotinic acetylcholine receptors in TE671 cells is also altered when the cells are differentiated, to produce a more neuronal nicotinic acetylcholine receptor type response rather than the muscle type. These findings provide potential human models of a variety of ionotropic glutamate receptors, which can be used in future research of these receptors, particularly in the pathophysiology of human disease, including schizophrenia, Alzheimer’s disease, and epilepsy. These diseases have previously been associated with a range of ionotropic glutamate receptors, but the associations are not fully understood, and so the models described here provide a valuable resource in future research of how such diseases are impacted by ionotropic glutamate receptors.